The Domestic Prices of Imported Commodities in Pakistan A Further Study (The Pakistan Development Review, 1968)
A system of effective quantitative restrictions on the supply of imported commodities will raise domestic prices of imports to levels well above their landed cost, i.e., price plus taxes, tariffs, and a normal markup. In 1965, Pal estimated the magnitude of such scarcity premia for a number of important commodities for East and West Pakistan [1; 2]1. His study has proved very useful both in measuring the influence of quantitative restrictions on the price of imports and, equally important, in showing the structure or incidence of restriction-induced profits—their distribution among consumption, intermediate and capital goods and their incidence relative to import policy. Pal's study was unavoidably static in nature and does not allow us to trace the changes over time. The purpose of the present paper is three-fold: first, to provide a comparison with Pal's study using data collected after two years and after a number of changes in Pakistan's import policies. This part of the analysis Is based strictly on Pal's commodity list. Second, in order to examine the impact of changing import composition, we shall recompute the scarcity premia on the basis of a new list of commodities and a changed set of weights (value of imports). Finally, we shall analyse the significance of the results for import control policy.